The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.7150/jca.56640
|View full text |Cite
|
Sign up to set email alerts
|

SNX-2112 Induces Apoptosis and Inhibits Proliferation, Invasion, and Migration of Non-Small Cell Lung Cancer by Downregulating Epithelial-Mesenchymal Transition via the Wnt/β-Catenin Signaling Pathway

Abstract: Lung cancer is the most frequent malignant tumor, and non-small cell lung cancer (NSCLC) is responsible for substantial mortality worldwide. The small molecule SNX-2112 was recently shown to critically effect the proliferation and apoptosis of tumor cells. Nevertheless, the precise mechanism by which SNX-2112 affects NSCLC remains poorly understood. Therefore, we investigated the function of SNX-2112 in NSCLC. We verified that SNX-2112 promoted apoptosis and suppressed the proliferation, invasion, and migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
5
1
Order By: Relevance
“…Studies have shown that the expression of p ‐GSK3β (SER9) is downregulated when the WNT pathway is closed, and that the downregulation of β‐catenin is a concomitant relationship rather than a causal relationship 33 . In the present study, 30,31,32,34,35,36 we found that p ‐GSK3β (SER389) is elevated when the WNT pathway is turned off, which is paradoxical with previous studies. In previous studies, it is generally believed that p ‐GSK3β (SER389), like p ‐GSK3β (SER9), is decreased when the WNT pathway is closed, whereas GSK3β (TYR216) 27 is increased, promoting the phosphorylation of β‐catenin and the final ubiquitination degradation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the expression of p ‐GSK3β (SER9) is downregulated when the WNT pathway is closed, and that the downregulation of β‐catenin is a concomitant relationship rather than a causal relationship 33 . In the present study, 30,31,32,34,35,36 we found that p ‐GSK3β (SER389) is elevated when the WNT pathway is turned off, which is paradoxical with previous studies. In previous studies, it is generally believed that p ‐GSK3β (SER389), like p ‐GSK3β (SER9), is decreased when the WNT pathway is closed, whereas GSK3β (TYR216) 27 is increased, promoting the phosphorylation of β‐catenin and the final ubiquitination degradation.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies have shown that the expression of p-GSK3β (SER9) is downregulated when the WNT pathway is closed, and that the downregulation of β-catenin is a concomitant relationship rather than a causal relationship. 33 In the present study, 30,31,32,34,35,36 we found that p-GSK3β (SER389) is elevated when the WNT pathway is turned off, which is paradoxical…”
Section: Discussionmentioning
confidence: 47%
“…A variety of human malignancies have been linked to dysregulation of the Wnt/β-catenin signaling pathway 22 24 . Inhibition of the Wnt signaling pathway can suppress NSCLC cell proliferation and xenograft growth, diminish cell migration and invasion, and generate a more differentiated phenotype, all of which are essential in NSCLC 25 28 . CTNNB1 accumulates in the nuclei of tumor cells when the Wnt signaling pathway is activated, resulting in the loss of epithelial integrity and increased tumor invasion and metastasis 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, overexpressing of β-catenin was able to rescuse the effect of FERMT2 on CRC cells. As reported that Wnt/β-catenin signaling pathway is one of the common upstream signals of EMT, and activation of this signaling pathway often induces EMT of cells in cancer [ 53 , 54 ]. FERMT2 may induce the expression of cyclin D1 and EMT related proteins by regulating the Wnt /β-catenin signaling pathway and promote the migration and invasion of CRC cells.…”
Section: Discussionmentioning
confidence: 99%